Design and build a library visitor monitoring system based on microcontrollers - Salung, Putri Ananda; Sujono, Sujono (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
The system combines microcontroller technology and sensors to develop an effective solution for monitoring library visitors. By utilizing hardware such as motion sensors and microcontrollers , this system can automatically identify and track visitors entering and exiting the library. The microcontroller-based visitor monitoring aims to design and construct an automatic library visitor monitoring system based on visitor entries and exits. This library visitor monitoring tool uses Ultrasonic Sensors to detect human objects, with a microcontroller as its controller, an LCD for displaying visitor data and a buzzer as an indicator for visitor entry and exit. The system operates automatically by counting the number of people entering or exiting the library space using Ultrasonic Sensors with a microcontroller as its controller. The Ultrasonic Sensors are placed beside the library entrance and exit doors. So, if a visitor passes through either of these paths at a certain range, the Ultrasonic Sensor will provide information about the incoming and outging visitors.